The Development of Problem Based Learning Geogebra-Assisted Teaching Materials to Improve Mathematics Communication Ability of Vocational School Students - Fitri Oviyani; Utari Sumarmo; Harry Dwi Putra ((JIML) JOURNAL OF INNOVATIVE MATHEMATICS LEARNING, 2022)
This study aims to produce teaching materials based on the GeoGebra-assisted Problem Based Learning approach that are valid, effective and practical to improve mathematical mathematical communication skills in linear programming material. The subjects in this study werw 30 students for a limited trial, 60 students for a broad trial, and 60 students for product testing including 30 experimental class and 30 control class. The instruments used in this study were interview sheets, student observation sheets on learning, response questionnaires to learning, validation questionnaires, five questions about mathematical communication ability tests, and non-test questionnaires for students' self-confidence. The results of this study indicate that the process of developing teaching materials is carried out well and the product is feasible to use, mathematical communication skills and self-confidence of students who receive learning using the GeoGebra-assisted Problem Based Learning method are better than students who receive learning using the usual approach, difficulties during learning do not indicate a high level of difficulty, in terms of mathematical communication problems students have difficulty in perfoming algebraic operations and more than half of students respond positively to learning.